A Comprehensive Review of Postoperative Management of Descemet's Membrane Endothelial Keratoplasty. (2nd January 2017) - Rapoport, Yuna; Veldman, Peter
ABSTRACT: Introduction : As Descemet's Membrane Endothelial Keratoplasty (DMEK) continues to gain in popularity, the postoperative management of DMEK surgery is becoming increasingly important, as these management strategies may affect postoperative success rates. Materials and Methods : This article reviews the current evidence for postoperative management in DMEK. Results : There are variable strategies in the postoperative management of DMEK as it relates to postoperative positioning, need for and timing of rebubble, tamponade agent utilized (both primarily and at rebubble), steroid agent and tapering schedule, timing of secondary regraft when required, and postoperative monitoring. Discussion : While a great deal of attention is rightly devoted to developing better surgical techniques for DMEK, we believe it is also crucial to develop a better understanding of and evidence-based best practice in the postoperative management of DMEK, as this may have important implications for outcomes.